TGF-Beta Receptor II Is Critical for Osteogenic Progenitor Cell Proliferation and Differentiation During Postnatal Alveolar Bone Formation - Xu, Chunmei; Xie, Xudong; Zhao, Hu; Wu, Yafei; Wang, Jun; Feng, Jian Q. (Frontiers in Physiology, 2021)
Transforming growth factor beta (TGFβ) signaling plays an important role during osteogenesis. However, most research in this area focuses on cortical and trabecular bone, whereas alveolar bone is largely overlooked. To address the role of TGFβR2 (the key receptor for TGFβ signaling) during postnatal alveolar bone development, we conditionally deleted Tgfβr2 in early mesenchymal progenitors by crossing Gli1-CreERT2; Tgfβr2flox/flox; R26RtdTomato mice (named early cKO) or in osteoblasts by crossing 3.2kb Col1-CreERT2; Tgfβr2flox/flox; R26RtdTomato mice (named late cKO). Both cKO lines were induced at postnatal day 5 (P5) and mice were harvested at P28. Compared to the control littermates, early cKO mice exhibited significant reduction in alveolar bone mass and bone mineral density, with drastic defects in the periodontal ligament (PDL); conversely, the late cKO mice displayed very minor changes in alveolar bone. Mechanism studies showed a significant reduction in PCNA+ PDL cell numbers and OSX+ alveolar bone cell numbers, as well as disorganized PDL fibers with a great reduction in periostin (the most abundant extracellular matrix protein) on both mRNA and protein levels. We also showed a drastic reduction in β-catenin in the early cKO PDL and a great increase in SOST (a potent inhibitor of Wnt signaling). Based on these findings, we conclude that TGFβ signaling plays critical roles during early alveolar bone formation via the promotion of PDL mesenchymal progenitor proliferation and differentiation mechanisms.